Advances in Environmental Research; Vol. 5 - Daniels J. A. Justin (New York, Nova Science Publishers, Inc., 2011)
Advances in Environmental Research is a journal for the publication of peer reviewed, original research in the fields of environmental science, engineering and technology. It includes full length research papers, case studies, notes and critical review papers reporting on major advances in areas that will: lead to improvements in or protection of the quality of the air, water and land environments, or improve the efficiency or cost effectiveness of existing technology, or contribute to our knowledge of transport and fate of pollutants in the environment. The primary aim of this Journal is to provide a vehicle for the rapid dissemination of information of interest to professionals in academia, industry, government and consulting who are involved in research in environmental quality control design and operation of waste treatment processes or plants remediation of contaminated sites process modification for pollution prevention or improved energy efficiency.This publication is designed to provide accurate and authoritative information with regard to the subject matter covered herein. It is sold with the clear understanding that the Publisher is not engaged in rendering legal or any other professional services.